Optimasi Web Log Menggunakan Teknik SEO On Page dan Off Page untuk Meningkatkan Trafik Pengunjung Organik - Ma'mur, Khaerul (KAKIFIKOM : Kumpulan Artikel Karya Ilmiah Fakultas Ilmu Komputer, 2023)
A website domain, whether it is webpage or a blog, is influenced by many factors to appear on the first page of the Search Engine Result Page (SERP). One of the determining factors are the application of Search Engine Optimization (SEO) techniques, which have a significant impact on website ranking. The better the application, the easier it is for a website or a blog to occupy the top position on the SERP and get organic visitor traffic every day. SEO optimization needs to be done so that a blog that is already in the top position or on the first page of search results is not displaced by competitor websites. Without applying SEO, search engines will have difficulty recognized web pages on the internet and can result in low visitor traffic to the website. There are generally two methods for SEO optimization, namely on-page and off-page methods. Both methods are combined to achieve the best ranking on the SERP, which can increase visitor traffic. The initial step is to analyze the web log that is being researched. The initial analysis of web log measurement using Google Analytics founds that organic visitors were below 100 per a day on average, affecting the quality of the SERP. Based on this condition, SEO optimization on-page and off-page needs to be measured. After implementing and optimizing both methods, the web log's visitor traffic reviewed for some time to determine the development of SEO techniques. The results showed an increase in visitor traffic by 40%.